THE INFUSION OF PROBLEM SOLVING SKILLS IN MICROLEARNING VIDEOS OF ENGLISH READING MATERIALS FOR NON-ENGLISH MAJOR - Dewanti, Ratna; Bontisesari, Bontisesari; Sulistyaningrum, Siti Drivoka (University of Kuningan, 2023)
Problem solving skills as one of the 21st century skills should strongly be focused in education because when students practice problem solving consistently, they can develop better social and situational awareness – the ones required in this social impact era. This study aimed at describing the infusion of problem solving skills in microlearning videos for non-English major students. In addition, it delineates the feasibility of the materials using a small-scale piloting. The study employs library research for the procedures of infusion and pilot study for the feasibility of the designed materials. The findings encompass detailed descriptions and procedures of the learning materials enclosed with a feasibility measurement conducted by a panel of three English learning materials experts and 50 participants as target users. The participants involved eleven English course instructors and thirty-nine students. The feasibility measures indicate that the microlearning video prototypes received satisfactory results. These results suggest that microlearning videos have the potential to enhance problem solving skills which in turns revamp the 21st century skills. The naturally determined characteristic of microlearning videos are also befitting the demand for bite-sized content of information, self-paced learning, mobile-friendly accessibility which undergo learning experience of students in digital era, especially in EFL context within higher education.